Why deprescribing antipsychotics in older people with dementia in long‐term care is not always successful: Insights from the HALT study. (15th July 2019) - Aerts, Liesbeth; Cations, Monica; Harrison, Fleur; Jessop, Tiffany; Shell, Allan; Chenoweth, Lynn; Brodaty, Henry
Abstract : Introduction: Antipsychotic medications are commonly used to manage behavioural and psychological symptoms of dementia despite their side effects and harms. While the Halting Antipsychotic Use in Long‐Term care (HALT) deprescribing trial was successful at reducing antipsychotic use, 19% of participants had their antipsychotics represcribed or never reached a dose of zero. The aim of this study was to investigate the reasons for represcription of antipsychotic medication and factors associated with ongoing antipsychotic use, relating to care staff requests and perceived behavioural changes. Materials and methods: Thirty‐nine of 133 HALT participants never ceased their antipsychotic medication or were represcribed a regular or pro re nata (PRN) antipsychotic after initial deprescribing. The views of nursing staff, general practitioner, and family on the circumstances leading up to these outcomes were collected via a questionnaire‐based approach. This information was triangulated with observation and detailed file audit (including progress notes, medical notes, medication charts, incident reports, and hospital discharge summaries). A consensus panel reconstructed the represcribing context. Results: Nurses were the most common drivers of represcribing (63.2%), followed by family members (39.5%), GPs (23.7%), specialists (13.2%), and hospital staff (10.5%). There were multiple drivers for antipsychotic use in 46.2% of participants. Increased agitated and aggressive behaviours were the most commonly reported reasons for represcribing even though these changes were not identified over time on objective measures. Consent and dosage practices remained poor despite education. Discussion: Nursing staff are the key drivers of deprescribing particularly in response to perceived worsening agitation and aggression among male residents. The train‐the‐trainer model used in the HALT trial may have been insufficient on its own to improve staff competence and confidence in applying nonpharmacological approaches when responding to behaviour change.